2018
DOI: 10.1177/0022034518790941
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Candida and Bacteriome in Children with Severe ECC

Abstract: Candida albicans is an opportunistic fungal organism frequently detected in the oral cavity of children with severe early childhood caries (S-ECC). Previous studies suggested the cariogenic potential of C. albicans, in vitro and in vivo, and further demonstrated its synergistic interactions with Streptococcus mutans. In combination, the 2 organisms are associated with higher caries severity in a rodent model. However, it remains unknown whether C. albicans influences the composition and diversity of the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 37 publications
6
108
0
6
Order By: Relevance
“…Recently, two NGS-based studies performed a cross-sectional comparison of SM in patients with SECC and children <5 yrs. Without caries, and both studies reported caries-associated characteristics of SM [50,51]. Notably, co-analysis of Candida albicans demonstrated that carriage of C. albicans in children with SECC attenuated the differences observed [51].…”
Section: Dental Cariesmentioning
confidence: 90%
“…Recently, two NGS-based studies performed a cross-sectional comparison of SM in patients with SECC and children <5 yrs. Without caries, and both studies reported caries-associated characteristics of SM [50,51]. Notably, co-analysis of Candida albicans demonstrated that carriage of C. albicans in children with SECC attenuated the differences observed [51].…”
Section: Dental Cariesmentioning
confidence: 90%
“…It is generally recognized that the mutans-group streptococci are the prime movers of the caries process due to their acidogenic and aciduric nature [10]. However, several studies have now shown that the aciduric oral yeasts, mainly belonging to Candida species, frequently co-inhabit these lesions with mutansstreptococci, and significantly contribute to the caries process [11][12][13][14]. There is also a substantial body of data to indicate cross-kingdom synergistic, interactions between this fungus and cariogenic CONTACT Lakshman Perera Samaranayake lsamaranayake@sharjah.ac.ae M28-125, College of Dental Medicine, University of Sharjah, Sharjah 27272, UAE bacteria within such polymicrobial-biofilm habitats [15,16] making the eukaryote a candidate caries pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…albicans, un organismo fúngico oportunista detectado con frecuencia en cavidad oral de niños con caries severas en primera infancia, puede presentar evolución aguda o crónica dependiendo de factores predisponentes, como estomatitis protética, queilitis angular, glositis romboidal y lengua vellosa. 21,22 Aunque las opciones de tratamiento son un proble-ma importante sobre todo por la toxicidad de los antifúngicos al hospedero y la resistencia que pueden ofrecer los microorganismos, frente a ello ha surgido el interés por la búsqueda de principios bioactivos a partir del veneno de arácnidos que ofrezcan mayor capacidad antimicrobiana, en la actualidad se tiene resultados que el veneno de es-corpión contiene péptidos que exhiben propiedades antimicrobianas y que además puede retardar la propagación de células cancerosas. 23,24 El veneno de escorpión H. charcasus perteneciente a la familia Caraboctonidae 16 , una de las especies de escorpiones que habitan en el norte del Perú.…”
Section: Resultados Discusiónunclassified